Load-Deflection Characteristics and Ultimate Load Capacity of Reinforced Concrete One-way Slab - AHALAJAL, MARY ANN; G. TRINIDAD, ARISTON; E. EMPIG, VICENTE; M. TRINIDAD, METODIA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study is conducted to investigate and compare the experimental load-deflection characteristics and ultimate load capacity of reinforced concrete one-way slab to the theoretical predictions. Six one-way slabs with dimensions 1000 mm x 150 mm x 50 mm, reinforced with 2-8 mm diameter main bars, were constructed. All specimens tested are simply supported beams subject to center-point load. The Universal Testing Machine is used to apply the load while the deflections of the slabs are measured using a dial indicator. The study reveals that the experimental deflections are 25% less than the theoretical deflections. The study also shows that the experimental ultimate load capacity of the slabs is 37% greater than the theoretical ultimate load capacity.